Afecciones bucales y la calidad de vida en preescolares de las instituciones educativas iniciales públicas de Iquitos - 2021 - Hidalgo Palacios, Frescia (2023)
Oral conditions are a global public health problem, Peru has a high prevalence that affects the child population in most cases. For this reason, it was necessary to demonstrate the relationship between oral conditions with the quality of life of preschool children from 3 to 5 years of age. The objective of the study was to determine the relationship of oral conditions with the quality of life in preschool children from 3 to 5 years of the public initial educational institutions of Iquitos, 2021. The sample consisted of 364 children from 3 to 5 years of age from the 26 public educational institutions in the district of Iquitos. The children's oral cavity was examined for dental caries, dentoalveolar trauma, and malocclusions. The instrument used was the (P-ECOHIS) questionnaire of the Peruvian version to evaluate the impact of oral conditions and dental treatments on the quality of life of children and their families), the same one that was answered by the parents. For the statistical analysis, the Kruskal-Wallis tests and the Mann-Whitney U test were used. To verify the distribution of the data, the Kolmogorov-Smirnov test was applied. The prevalence of dental caries was 69%, malocclusions 55, 5%, trauma 8%. The study found a high statistical significance only between dental caries and the impact on the quality of life of children and parents (p?0.000). It is concluded that the presence of caries is associated with a worse quality of life for children and family.